Clinicopathological of Pre-Operative Thrombocytosis in Epithelial Ovarian Cancer - Sugandi, Catherine; Maulida, Widya; Hutapea, Manuel (Indonesian Journal of Obstetrics and Gynecology, 2024)
Abstract Objective: To investigate the clinicopathological of preoperative thrombocytosis in patients with epithelial ovarian cancer at dr. Soedarso Regional General Hospital Pontianak. Methods: A cross-sectional retrospective study was conducted over three months from January 2022 to March 2022, and bivariate analysis was performed using the Chi-Square test. Results: A total of 28 subjects met the inclusion criteria, with 19 subjects had thrombocytosis (67.9%) and 9 subjects did not experience thrombocytosis (32.1%). Meanwhile, the results of the Chi Square Test showed a relationship between thrombocytosis and histopathological type in the subjects (p=0.036). Conclusion: Preoperative thrombocytosis is associated with the histopathological type of epithelial ovarian cancer at dr. Soedarso Regional General Hospital Pontianak. Keywords: epithelial ovarian cancer, histopathology, stage, thrombocytosis